5G mmWave patch antenna array with proximity sensing function for detecting user's hand grip on mobile terminals - Jeong‐Ung Yoo; Hae‐Won Son (Electronics Letters, 2023)
Abstract We propose a new concept millimetre‐wave patch antenna that integrates the functions of an antenna and a capacitive proximity sensor to detect the hand grip state for 5G mobile terminals and compensate for the hand effect. The proposed antenna has the structure of a proximity‐coupled fed patch and functions as a proximity sensor by using the capacitance change of the patch that occurs when the user's hand approaches the patch. By observing the capacitance change at the centre of the patch operating in the TM01 mode, it is possible to simultaneously perform the functions of antenna and sensor without mutual interference. The proposed antenna is implemented as a 1 × 4 array. The experimental results show that it has a stable gain of 8.3 to 10.1 dBi at 26.5 to 29.5 GHz and can operate as a proximity sensor with a capacitance change of 200 fF according to the proximity of the hand.